De-islamization in java during the Dutch colonial period from 1800 to 1942 - Priyoyudanto, Febri; Wan Sulong, Wan Suhana (IIUM Press, International Islamic University Malaysia, 2017)
The very long period of Dutch colonialism in Indonesia still has a very significant impact on Indonesia, including on Java as part of Nusantara. Javanese people as the largest population in Indonesia were greatly affected by the de-Islamization process during the Dutch colonial period. This process not only estranged Javanese people from Islamic values, but the culture of Hindu-Buddhism was seen as a major variable in Javanese culture. Although the Dutch colonists encouraged systematic deIslamization efforts, Javanese Muslims provided resistance in many ways. This book intends to examine the de-Islamization efforts in Java during the Dutch colonial period. It focuses on the Javanese ethnic group on Java Island, Indonesia. The findings are useful in understanding the patterns and strategy for de-Islamization which were created by the Dutch during the colonial period. The method of data collection used in this book was documentary research. The information was gathered from books, journals, and websites pertaining to the Dutch colonial history of Java. In order to enhance comprehension of this topic, the authors surveyed Javanese culture, educational and cultural de-Islamization, Islamic revivalism and resistance to political de-Islamization in Java during the Dutch colonial period.